2007
DOI: 10.1007/s10750-007-9149-3
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate drift density in relation to abiotic factors in the Missouri River

Abstract: Changes in flow management to restore ecosystem health have been proposed as part of many restoration projects for regulated rivers. However, uncertainty exists about how the biota will respond to flow management changes. The objectives of this study were to estimate the relative importance of key abiotic predictor variables to aquatic macroinvertebrate drift densities in the Missouri River and to compare these results among reaches of the river. A multi-year, multi-location database of spring macroinvertebrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 45 publications
2
26
0
4
Order By: Relevance
“…In each simulation year, initial prey biomass in each grid cell is randomly assigned on January 1st with a mean of 18.8 wet g m −2 (±2.2 SE), which was derived from field studies conducted near the study system (the Platte and Missouri Rivers, Hay et al, 2008;Whiles and Goldowitz, 2001; with a wet to dry weight conversion factor of 0.145 (Cummins and Wuycheck, 1971 …”
Section: Input Datamentioning
confidence: 99%
“…In each simulation year, initial prey biomass in each grid cell is randomly assigned on January 1st with a mean of 18.8 wet g m −2 (±2.2 SE), which was derived from field studies conducted near the study system (the Platte and Missouri Rivers, Hay et al, 2008;Whiles and Goldowitz, 2001; with a wet to dry weight conversion factor of 0.145 (Cummins and Wuycheck, 1971 …”
Section: Input Datamentioning
confidence: 99%
“…Aquatic ecosystems are essential for the development of human societies, offering goods and services of fundamental importance, such as water supply, flood control, transportation, and power generation (Hay et al, 2008;Arthington et al, 2010). However, rivers have suffered countless influences of human activities, primarily from waste releases, introductions of alien species, construction of barriers, and alteration of flow regimes (Agostinho et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…The abiotic changes resulting from dams, reservoirs, and flow alterations can change important biotic parameters, including benthic macroinvertebrate Hay et al, 2008) and fish (Rinne et al, 2005;Pompeu et al, 2012) assemblages. The reduction of substrate heterogeneity reduces the diversity of available habitats for macroinvertebrates, decreasing their abundance and diversity (Patterson and Smokorowski, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Seasonal or other short-term temporal variation has been examined indirectly, if at all, in the recent large river studies we reviewed. Hay (2006) reported that total drift density in the Missouri River was positively correlated with degree-days. Also in the Missouri River, Grohs (2008) noted higher total richness in the summer and fall, but discriminatory power was limited by family-level identifications.…”
Section: Introductionmentioning
confidence: 99%